PENGARUH PENGUNGKAPAN DIRI DAN PENYESUAIAN PERNIKAHAN TERHADAP KUALITAS PERNIKAHAN PASANGAN DENGAN CARA TAâ€™ARUF - Hanifatusholihah Hani; Theresia Indira Shanti (MANASA, 2023)
Â Marriage through the method of â€œtaâ€™arufâ€ has become popular recently. Considering that the process of marriage conducted thorugh â€œtaâ€™arufâ€ is different from the conventional marriage process, it is interesting to examine it from the perspectives of self disclosure and marital adjustment. The aim of this study is to describe the influence of self disclosure and marital adjustment on the marital quality of couples who undergo â€œtaâ€™arufâ€ marriage. The study employs a quantitative approach, and the participants consist of 32 respondents who are married through the â€œtaâ€™arufâ€ method, comprising both males and females. Three measurements are utilized in this study: The Indonesian Moslem Marital Quality Scale; Self Disclosure and Relational Outcomes; and the Marital Adjustment Questionnaire. Multiple regression analysis is used as the analytical method to test the hypotheses. The findings show a significant influence of self disclosure on the marital quality of couples who marry through the â€œtaâ€™arufâ€ method. Marital adjustment also significantly affects the marital quality of such couples. Also both self disclosure and marital adjustment have an impact on the marital quality of couples who undergo â€œtaâ€™arufâ€ marriage. The implications of this study suggest that couples who marry through â€œtaâ€™arufâ€ can achieve good marital quality similar to couples who opt for other methods. However, it is advisable for prospective couples who are still in the â€œtaâ€™arufâ€ process to go deeper into understanding each other and seek information from books or literature about marriage in Islam as an effort to prepare for a higher quality marriage.